2007
DOI: 10.1007/s10540-007-9058-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome Re-duplication and Irregular Segregation Occur During the Cell Cycle of Entamoeba histolytica

Abstract: Heterogeneity of genome content is commonly observed in axenic cultures of Entamoeba histolytica. Cells with multiple nuclei and nuclei with heterogenous genome contents suggest that regulatory mechanisms that ensure alternation of DNA synthesis and mitosis are absent in this organism. Therefore, several endo-reduplicative cycles may occur without mitosis. The data also shows that unlike other endo-reduplicating organisms, E.histolytica does not undergo a precise number of endo-reduplicative cycles. We propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…It has been suggested that surveillance mechanisms or checkpoints regulating alternation of genome duplication and cell division are altered or absent in E. histolytica. Sequence homologous to several cell cycle regulating proteins have been identified in amoeba, but their structural divergence suggests that they may not have equivalent function in this organism (Banerjee et al, 2002;Lohia, 2003;Loftus et al, 2005;Lohia et al, 2007). Constitutive association of the evolutionary conserved EhMcm2-3-5 proteins with chromatin could be one of the reasons why genome reduplication occurs in E. histolytica (Das et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that surveillance mechanisms or checkpoints regulating alternation of genome duplication and cell division are altered or absent in E. histolytica. Sequence homologous to several cell cycle regulating proteins have been identified in amoeba, but their structural divergence suggests that they may not have equivalent function in this organism (Banerjee et al, 2002;Lohia, 2003;Loftus et al, 2005;Lohia et al, 2007). Constitutive association of the evolutionary conserved EhMcm2-3-5 proteins with chromatin could be one of the reasons why genome reduplication occurs in E. histolytica (Das et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Log-phase cultures may accumulate multinucleated cells containing heterogeneous amounts of DNA (12,18). Our previous observations suggest that genome reduplication without mitosis and irregularity in cytokinesis contribute maximally to the observed heterogeneity (12,36). We have also observed that sequence homologs of several eukaryotic "checkpoint proteins" are not found in the amoeba genome (36).…”
mentioning
confidence: 90%
“…Our previous observations suggest that genome reduplication without mitosis and irregularity in cytokinesis contribute maximally to the observed heterogeneity (12,36). We have also observed that sequence homologs of several eukaryotic "checkpoint proteins" are not found in the amoeba genome (36). However, functional analysis of a kinesin-like protein, E. histolytica Klp5 (Klp5 Eh ), showed that increased expression of this protein, while promoting microtubular spindles, leads to homogenization of the average DNA content in growing cells (13).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…histolytica has been shown to occur along the microtubular assemblies without disruption of the nuclear envelope [20,21]. Occurrence of multinucleated cells in cell culture suggested duplication and reduplication of nuclear DNA without cytokinesis [22,23]. Although Kinesin like protein (Klp1), Formin1 and EhCaBP6 were shown to be part of the microtubular assembly [19,24,25], their role in regulation of the cell cycle is not yet documented.…”
Section: Introductionmentioning
confidence: 99%